EPISTOLA BOTANICA: MAYACACEAE IN INDONESIA: AN ALIEN FAMILY ESCAPED FROM CULTIVATION - Muhammad Rifqi Hariri; Muhammad Hisyam Fadhil; Arifin Surya Dwipa Irsyam; Dian Rosleine; Rina Ratnasih Irwanto (PTTI, 2023)
Mayacaceae Kunth is a monogeneric family with a single genus, Mayaca Aubl. Its family members are herbs found in swamps, lakes, and rivers. The family is distributed throughout the Neotropics, except for M. baumii Gürke, which is only found in Africa [de Carvalho MLS & Machado AFP., Revisiting Mayacaceae Kunth towards to future perspectives in the family, Rodriguésia 66(2): 421-427. 2015]. Mayacaceae consists of ten species and one of them, Mayaca fluviatilis Aubl. is widely cultivated as an aquascape ornamental plant, including in Indonesia. This aquatic family is not yet recorded in the Flora of Java Vol. III [Backer CA & Bakhuizen van den Brink RC., Flora of Java, Vol. III, Groningen: NVP Noordhoff. 1968].